Emotion Regulation In Relation To Adolescent Prosocial Behavior In Terms Of Gender - Handayani, Wiwik ; Chai, Nong; Lima, Lucas; Khan, Omar (International Journal of Research in Counseling, 2025)
Background. Adolescence is a critical period for emotional development and social adjustment. During this stage, the ability to regulate emotions becomes increasingly important, particularly as it influences the formation of prosocial behavior—actions intended to benefit others. Gender differences have also been observed in both emotional regulation strategies and prosocial tendencies, highlighting the need to explore how these variables interact. Purpose. This quantitative study aimed to investigate the relationship between emotion regulation and prosocial behavior in adolescents, with a specific focus on gender differences. It also sought to identify whether gender moderates the influence of emotion regulation strategies on the development of prosocial actions among adolescents. Method. The study involved 320 high school students aged 13–17 from urban and semi-urban schools. Data were collected using standardized psychological scales measuring emotion regulation (including cognitive reappraisal and expressive suppression) and prosocial behavior. Statistical analysis was conducted using correlation analysis, multiple regression, and moderation tests to examine gender-based differences. Results. The findings revealed a significant positive correlation between cognitive reappraisal and prosocial behavior in both genders, with a stronger effect observed among female participants. Expressive suppression showed a weak or negative correlation with prosocial behavior, particularly among males. Gender was found to moderate the relationship, indicating that females who engage in positive emotion regulation strategies tend to display higher levels of prosocial behavior. Conclusion. Emotion regulation plays a crucial role in shaping adolescent prosocial behavior, with notable differences between males and females. Educational and psychological interventions aimed at fostering emotional competence should consider gender-specific approaches to enhance social functioning and empathy among adolescents.